A focus on the use of subcutaneous C1-inhibitor for treatment of hereditary angioedema. (3rd May 2020) - Villavicencio, Maria Fernanda; Craig, Timothy
ABSTRACT: Introduction: HAE is a very debilitating disease that causes significant distress for patients not only during an acute attack but also constant fear for a subsequent attack. It is important to address long-term prophylactic (LTP) therapy to prevent attacks, decrease morbidity and increase the quality of life. When discussing LTP, the drug burden, convenience and efficacy must be taken into account. Areas covered: We review the literature and the different phases of clinical trials leading up to approval by the US FDA of subcutaneous highly concentrated C1-Inhibitor (SC-C1-INH), called Haegarda. The dose approved is of 60 IU/kg twice weekly showing significant improvement in the reduction of attacks and need for on-demand therapy for attacks with minimal side effects. Expert opinion: SC-C1-INH has added significantly to the armamentarium of physicians that treat HAE. The ability to achieve a steady state of C1-INH above 40% function is key to the success of the drug. The drug burden is an SC injection twice a week that exceeds the newly approved lanadelumab. The benefit may be that the protein that is deficient in HAE is replaced and with this the complement, fibrinolytic, coagulation pathways, and contact system are also regulated; however, evidence that this is of benefit is still lacking.